(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to Translate and Validate the Questionnaire of Self-Concept by (Dolejš et al., 2022) on young adults in Saudi Society. The study adopts a descriptive-analytical methodology. The sample consisted of (200) of young adults (male-female) in Saudi Society during the year 2024-2025. The study used the following tools after obtaining the voluntary consent from the participants, which are as follows: Questionnaires of Demographic Questions (by researcher), Questionnaires of Self-Concept-18 (Dolejš et al., 2022) Translation to Arabic: (Albukhari et al., 2026). The results demonstrated that the Arabic version of the Questionnaires of Self-Concept-18 possesses good psychometric properties, including its suitability for application among young adults in Saudi Society. Based on the findings of the present study the researcher highlights the necessity of developing programs focused on self-concept clarity, while fostering a stimulating environment that promotes positive self-concept among young adults in Saudi Society.